Vascular injury is associated with repetitive head impacts and tau pathology in chronic traumatic encephalopathy. Issue 2 (6th January 2023) - Kirsch, Daniel; Shah, Arsal; Dixon, Erin; Kelley, Hunter; Cherry, Jonathan D; Xia, Weiming; Daley, Sarah; Aytan, Nurgul; Cormier, Kerry; Kubilus, Carol; Mathias, Rebecca; Alvarez, Victor E; et al.
Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease linked to repetitive head impacts (RHI) and characterized by perivascular hyperphosphorylated tau (p-tau) deposits. The role of vascular injury, blood-brain barrier leakage, and neuroinflammation in CTE pathogenesis is not well understood. We performed quantitative immunoassays for intercellular adhesion molecule 1 (ICAM1), vascular cellular adhesion molecule 1 (VCAM1), and C-reactive protein (CRP) within the postmortem dorsolateral frontal cortex of participants with and without a history of RHI and CTE (n  =  156), and tested for associations with RHI, microgliosis, and tau pathology measures. Levels of vascular injury-associated markers ICAM1, VCAM1, and CRP were increased in CTE compared to RHI-exposed and -naïve controls. ICAM1 and CRP increased with RHI exposure duration (p < 0.01) and were associated with increased microglial density (p < 0.001) and tau pathology (AT8, p-tau396, p-tau202; p < 0.05). Histologically, there was significantly increased ICAM1 staining of the microvasculature, extracellular space, and astrocytes at the sulcal depths in high stage CTE compared to both low stage CTE and controls. Multifocal perivascular immunoreactivity for serum albumin was present in all RHI-exposed individuals. These findings demonstrate that vascular injury markers are associated with RHI exposure, duration, and microgliosis, are elevated in CTE, and increase with disease severity.